Effects of blood flow restriction training on cognitive flexibility in adolescent volleyball players - Liu, X.; Xiao, J.; Chen, H. (Perceptual and Motor Skills, 2025)
Cognitive flexibility is crucial for volleyball athletes, enabling swift adaptation to dynamic game situations. While blood flow restriction (BFR) training has been suggested to enhance working memory, its specific effects on cognitive flexibility in volleyball players are not well understood. Therefore, this study investigates the effects of BFR combined with low-intensity aerobic exercise on cognitive flexibility in adolescent athletes, with a focus on the role of peripheral catecholamines. A randomized balanced crossover design was employed, involving 20 participants who completed four intervention conditions: sedentary rest, low-intensity aerobic exercise, moderate-intensity aerobic exercise, and BFR with low-intensity aerobic exercise. Post-intervention assessments included measurements of peripheral catecholamine levels and cognitive flexibility, specifically examining shifting costs. The results revealed significant differences in shifting costs across intervention conditions (p < .001). BFR training was associated with significantly higher shifting costs compared to sedentary rest (p < .001), lowintensity aerobic exercise (p < .001), and moderate-intensity aerobic exercise (p = .003). Correlation analysis demonstrated significant negative associations between post-BFR norepinephrine (R = -0.46) and epinephrine (R = -0.48) levels and shifting costs. These findings highlight the potential of BFR training to improve cognitive flexibility in adolescent volleyball players beyond the effects of moderate-intensity aerobic exercise, with practical implications for optimizing training regimens in this population. Additionally, the observed correlations between norepinephrine and epinephrine levels and cognitive performance offer novel insights into the physiological mechanisms underpinning cognitive function in sports contexts.